Assistência ginecológica a homens trans na Atenção Primária à Saúde: barreiras de acesso e a garantia do cuidado integral - Fernanda Oliveira Prado; Maria Clara Silvério Gonçalves; Hárllen Éric Benevides de Castro; Isnaya Teixeira Araújo (Revista ft, 2026)
Providing preventive gynecological care to trans men within Primary Health Care poses a challenge to ensuring comprehensive care, given the structural, organizational, and interpersonal barriers present in health services. This study aimed to analyze the main challenges regarding trans men's access to and continued engagement with preventive gynecological care offered by Primary Health Care. It is a secondary study conducted through a bibliographic survey and an integrative literature review. Searches were performed in the SciELO and LILACS databases (via the Virtual Health Library portal) and PubMed/MEDLINE, using controlled descriptors and free-text terms related to transgender men, primary health care, cervical cancer screening, and gynecological care. The study included full-text articles published in Portuguese, English, and Spanish that were indexed in the selected databases within the last ten years. The results highlighted the following key barriers: service cisnormativity, prejudice, discrimination, disrespect regarding social names and pronouns, professional unpreparedness, inadequate protocols, and difficulties associated with gynecological procedures. The study concludes that expanding trans men's access to and retention in gynecological care requires ongoing staff training, service reorganization, the adoption of inclusive protocols, and the assurance of practices grounded in the principles of universality, comprehensiveness, and equity.